Impact of kinesiophobia (fear before movement) to physical activity level in patients with artery hypertension - Janusz Kocjan (Kazimierz Wielki University, 2015)
Kocjan Janusz. Impact of kinesiophobia (fear before movement) to physical activity level in patients with artery hypertension. Journal of Education, Health and Sport. 2015;5(4):309-318. ISSN 2391-8306. DOI: 10.5281/zenodo.17154 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A309-318 https://pbn.nauka.gov.pl/works/555232 http://dx.doi.org/10.5281/zenodo.17154 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015.   IMPACT OF KINESIOPHOBIA (FEAR BEFORE MOVEMENT) TO PHYSICAL ACTIVITY LEVEL IN PATIENTS WITH ARTERY HYPERTENSION   Janusz Kocjan   Faculty of Medicine, Medical University of Silesia, Katowice, Poland   SUMMARY Introduction: Insufficient level of physical activity is presence in general populations as well as in patients suffer from various somatic diseases. However still is little known about risk factors of hypokinesia. To date, lack is a study directly designed to assess impact of kinesiophobia to physical activity level in patients with artery hypertension. Aim: The aim of the study was to evaluate the degree of kinesiophobia and physical activity level in patients with arterial hypertension and examine the relationship between kinesiophobia level and physical activity level. Material and methods: A total of 88 (Mage=59,46, SDage=9,16) patients with diagnosed hypertension were examined. Following polish version of questionnaires were used: Kinesiophobia Causes Scale (KCS) and Habitual Physical Activity (HPA). Results: Low level of physical activity and moderate intensity of kinesiophobia were noted. Moderate and strong correlations between domains and factors of kinesiophobia with physical activity domains were found. In addition, significant correlations between time since hypertension diagnosis with physical activity and kinesiophobia domains were also reported. High level of kinesiophobia was significantly associated with high level of physical inactivity. Conclusions: Kinesiophobia may be an important factor contributing to limitation of physical activity and can play a significant role in modulation of physical activity level.   Key words: kinesiophobia, fear before movement, physical activity, hypertension.